Pairing symmetries in cuprates: A Gorkov formalism - Ghosh, Angsula; Pimentel, B. M. [UNESP] (Elsevier B.V., 2012)
Inspite of the direct evidence for Cooper pairing in the cuprates as in conventional superconductors, the pairing symmetry in the cuprate superconductors is still considered to be a controversial and a highly debatable topic. The microscopic equations appropriate for these new materials, essentially the yttrium based compounds, are discussed following Gorkov's formalism for the conventional superconductors. Various types of symmetry of the pairing parameter are considered. In this study we consider the anisotropic nature of the gap parameter to write the mean-field equations of the cuprates. We observe that the symmetry of the potential is fundamental in deciding the nature of the anisotropy in the gap parameter. (C) Elsevier B.V. All rights reserved.
Keywords: Cuprate; Cooper pairing; Pairing symmetry